Evaluación del potencial interpretativo de los recursos de los sitios de excursionismo del cantón Pujilí, provincia de Cotopaxi. - Almache Cherrez, Anthony Alexis (2023)
This research work was carried out in Pujilí canton, Cotopaxi Province, with the objective of evaluating the interpretive potential index (IPI) of the resources in the canton's hiking sites for sustainable use. The research has a qualitative approach and descriptive scope, through the application of interviews that allowed a statistical analysis and justification of these. In the first objective, the technique of mapping actors in the area of tourism was applied in which interviews were conducted with personnel from the cantonal and parish autonomous decentralized governments, national guides and tour operators, which resulted in the identification of 20 hiking sites, each of which were evaluated and justified with the parameters described by the authors (Morales & Lozano, 2010) for the discarding of sites, which resulted in only 9 sites that met all the requirements. In the second objective, the inductive, descriptive, exploratory and direct observation method was used, with techniques such as the card to qualify each natural and cultural resource in the 9 hiking sites accompanied by the scoring table to determine the index of interpretive potential (IPI), the IPI scale, inventory of the physical conditions of these sites and georeferencing mapping, This methodology was based on the 9 criteria established in the IPI sheet by the authors (Morales & Lozano, 2010), which resulted in a score of 34.2 in Quilotoa la Playita with a high (IPI), then Quilotoa Vuelta al Cráter with 33.1 with a high (IPI), these two places obtained the highest score of the 9 sites evaluated. The third objective used the inductive and analytical method with the SWOT analysis technique, based on the authors (Ponce Talancón & Santo Tomás, 2007), analyzed the strengths, opportunities, weaknesses and threats in aspects such as (accessibility, signage, adequacy, attractiveness, promotion and competition) of the sites, followed by a search for internal strengths and weaknesses (MEFI), as well as external opportunities and threats (MEFE), where each one was given a weight of 0. 0 -1.0, and a score between 1 and 4 to obtain a weighted result (MEFI) of 2.91 and (MEFE) of 3.56. After this, the internal external matrix (MIE) was prepared and with these scores obtained in the previous matrices, it was decided to propose strategies for growth and tourism development that were reflected in the strategic matrix in which one of the proposed strategies is the incorporation of panels and tourist signage, for the development of the strategy took into account strengths with opportunities (FO), weaknesses with opportunities (DO), strengths with threats (FA), and weaknesses with threats (DA), this strategy focuses on improving hiking sites for the canton. It is concluded that in the canton of Pujilí there are hiking sites with a high IPI score and sites with a low IPI, so it is recommended that the strategy of incorporating panels and tourist signage be applied in the hiking sites with lower weighting so that they can be used in an adequate manner